Pemanfaatan Sampah Domestik di Lingkungan Desa Sukunan - Dandi Subandi (Prosiding Sains dan Teknologi, 2022)
This study seeks information about waste management, Sukunan Village can manage waste independently. The purpose of this study was to determine the process of managing domestic waste in the Sukunan Village environment and to find out the waste treatment carried out in the Sukunan Village environment. The type of method used in this research is descriptive, by providing a clear picture with the main focus being to reveal a problem and the situation as it is. Methods of data collection is done by field studies or observation and documentation. Data obtained by observing directly at the research site. Sources of data obtained from primary and secondary data. Sukunan Village has been processing its waste independently since 2003 until now. The village, which was inaugurated as a tourist village in 2009, has a well-structured waste management system and has benefits that have a direct impact on the residents of Sukunan village. The use of waste in Sukunan Village is very diverse, ranging from being converted into crafts and fertilizers which are very useful for the residents of Sukunan Village. Various types of household waste can be utilized, such as plastic waste, paper, glass, metal, to organic food waste and plantation waste. Keywords: Utilization, Domestic Waste, Sukunan Village